A Day 14 Endpoint for Acute GVHD Clinical Trials - Spyrou, Nikolaos; Akahoshi, Yu; Kowalyk, Steven; Morales, George; Beheshti, Rahnuma; Aguayo-Hiraldo, Paibel; Al Malki, Monzr M.; Ayuk, Francis; Bader, Peter; Baez, Janna; Capellini, Alexandra; Choe, Hannah; et al. (Transplantation and Cellular Therapy, 2024)
The overall response rate (ORR) 28 days after treatment has been adopted as the primary endpoint for clinical trials of acute graft versus host disease (GVHD). However, physicians often need to modify immunosuppression earlier than day (D) 28, and non-relapse mortality (NRM) does not always correlate with ORR at D28. We studied 1144 patients that received systemic treatment for GVHD in the Mount Sinai Acute GVHD International Consortium (MAGIC) and divided them into a training set (n=764) and a validation set (n=380). We used a recursive partitioning algorithm to create a Mount Sinai model that classifies patients into favorable or unfavorable groups that predicted 12 month NRM according to overall GVHD grade at both onset and D14. In the Mount Sinai model grade II GVHD at D14 was unfavorable for grade III/IV GVHD at onset and predicted NRM as well as the D28 standard response model. The MAGIC algorithm probability (MAP) is a validated score that combines the serum concentrations of suppression of tumorigenicity 2 (ST2) and regenerating islet-derived 3-alpha (REG3α) to predict NRM. Inclusion of the D14 MAP biomarker score with the D14 Mount Sinai model created three distinct groups (good, intermediate, poor) with strikingly different NRM (8%, 35%, 76% respectively). This D14 MAGIC model displayed better AUC, sensitivity, positive and negative predictive value, and net benefit in decision curve analysis compared to the D28 standard response model. We conclude that this D14 MAGIC model could be useful in therapeutic decisions and may offer an improved endpoint for clinical trials of acute GVHD treatment.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Acute GVHD; Biomarkers; Classification and regression tree; Competing risk; Competing risks; Composite; Decision curve analysis; Endpoints; Immunosuppression; Machine learning; Nonrelapse mortality; Surrogate; Time-dependent AUC; Treatment response

Adoptive transfer of donor B lymphocytes: a phase 1/2a study for patients after allogeneic stem cell transplantation. - Winkler, Julia; Tittlbach, Hannes; Schneider, Andrea; Vasova, Ingrid; Strobel, Julian; Herold, Susanne; Maas, Stefanie; Spriewald, Bernd; Repp, Roland; Kordelas, Lambros; Mach, Michael; Wolff, Daniel; et al. (Blood Advances, 2024)
Immune reconstitution after allogeneic hematopoietic stem cell transplantation (allo-HSCT) is slow and patients carry a high and prolonged risk of opportunistic infections. We hypothesized that the adoptive transfer of donor B cells can foster after HSCT immuno-reconstitution. Here, we report, to our knowledge, the results of a first-in-human phase 1/2a study aimed to evaluate the feasibility and safety of adoptively transferred donor B cells and to test their activity upon recall vaccination. Good manufactoring practice (GMP) B-cell products were generated from donor apheresis products using 2-step magnetic cell separation. Fifteen patients who had undergone allo-HSCT were enrolled and treated after taper of immunosuppression (median, day +148; range, 130-160). Patients received 4 different doses of B cells (0.5 × 106 to 4.0 × 106 B cells per kg body weight). To test the activity of infused donor memory B cells in vivo, patients were vaccinated with a pentavalent vaccine 7 days after B-cell transfer. We observed the mobilization of plasmablasts and an increase in serum titers against vaccine antigens, with a stronger response in patients receiving higher B-cell numbers. Analysis of immunoglobulin VH-sequences by next-generation sequencing revealed that plasmablasts responding to vaccination originated from memory B-cell clones from the donor. Donor B-cell transfer was safe, as no Epstein-Barr virus (EBV) reactivation was observed, and only low-grade graft-versus-host disease (GVHD) occurred in 4 out of 15 patients. This pilot trial may pave the way for further studies exploring the adoptive transfer of memory B cells to reduce the frequency of infections after allo-HSCT. This trial was registered at ClinicalTrial.gov as #NCT02007811.
EVALuna2:562572

Amphiregulin, ST2, and REG3α biomarker risk algorithms as predictors of nonrelapse mortality in patients with acute GVHD - Etra, Aaron; Jurdi, Najla El; Katsivelos, Nikolaos; Kwon, Deukwoo; Gergoudis, Stephanie; Morales, George; Spyrou, Nikolaos; Kowalyk, Steven; Aguayo-Hiraldo, Paibel; Akahoshi, Yu; Ayuk, Francis; Baez, Janna; et al. (Blood Advances, 2024)
Graft-versus-host disease (GVHD) is a major cause of nonrelapse mortality (NRM) after allogeneic hematopoietic cell transplantation. Algorithms containing either the gastrointestinal (GI) GVHD biomarker amphiregulin (AREG) or a combination of 2 GI GVHD biomarkers (suppressor of tumorigenicity-2 [ST2] + regenerating family member 3 alpha [REG3α]) when measured at GVHD diagnosis are validated predictors of NRM risk but have never been assessed in the same patients using identical statistical methods. We measured the serum concentrations of ST2, REG3α, and AREG by enzyme-linked immunosorbent assay at the time of GVHD diagnosis in 715 patients divided by the date of transplantation into training (2004-2015) and validation (2015-2017) cohorts. The training cohort (n = 341) was used to develop algorithms for predicting the probability of 12-month NRM that contained all possible combinations of 1 to 3 biomarkers and a threshold corresponding to the concordance probability was used to stratify patients for the risk of NRM. Algorithms were compared with each other based on several metrics, including the area under the receiver operating characteristics curve, proportion of patients correctly classified, sensitivity, and specificity using only the validation cohort (n = 374). All algorithms were strong discriminators of 12-month NRM, whether or not patients were systemically treated (n = 321). An algorithm containing only ST2 + REG3α had the highest area under the receiver operating characteristics curve (0.757), correctly classified the most patients (75%), and
CRIS-Team Scopus Importer:2024-07-12

CAR T-cell therapy rescues adolescent with rapidly progressive lupus nephritis from haemodialysis - Krickau, Tobias; Naumann-Bartsch, Nora; Aigner, Michael; Kharboutli, Soraya; Kretschmann, Sascha; Spörl, Silvia; Vasova, Ingrid; Völkl, Simon; Wölfle, Joachim; Mackensen, Andreas; Schett, Georg; Metzler, Markus; et al. (Lancet, 2024)
CRIS-Team Scopus Importer:2024-05-03

CD19 CAR T-Cell Therapy in Autoimmune Disease - A Case Series with Follow-up. - Müller, Fabian; Taubmann, Jule; Bucci, Laura; Wilhelm, Artur; Bergmann, Christina; Völkl, Simon; Aigner, Michael; Rothe, Tobias; Minopoulou, Ioanna; Tur, Carlo; Knitza, Johannes; Kharboutli, Soraya; et al. (New England Journal of Medicine, 2024)
BACKGROUND: Treatment for autoimmune diseases such as systemic lupus erythematosus (SLE), idiopathic inflammatory myositis, and systemic sclerosis often involves long-term immune suppression. Resetting aberrant autoimmunity in these diseases through deep depletion of B cells is a potential strategy for achieving sustained drug-free remission. METHODS: We evaluated 15 patients with severe SLE (8 patients), idiopathic inflammatory myositis (3 patients), or systemic sclerosis (4 patients) who received a single infusion of CD19 chimeric antigen receptor (CAR) T cells after preconditioning with fludarabine and cyclophosphamide. Efficacy up to 2 years after CAR T-cell infusion was assessed by means of Definition of Remission in SLE (DORIS) remission criteria, American College of Rheumatology-European League against Rheumatism (ACR-EULAR) major clinical response, and the score on the European Scleroderma Trials and Research Group (EUSTAR) activity index (with higher scores indicating greater disease activity), among others. Safety variables, including cytokine release syndrome and infections, were recorded. RESULTS: The median follow-up was 15 months (range, 4 to 29). The mean (±SD) duration of B-cell aplasia was 112±47 days. All the patients with SLE had DORIS remission, all the patients with idiopathic inflammatory myositis had an ACR-EULAR major clinical response, and all the patients with systemic sclerosis had a decrease in the score on the EUSTAR activity index. Immunosuppressive therapy was completely stopped in all the patients. Grade 1 cytokine release syndrome occurred in 10 patients. One patient each had grade 2 cytokine release syndrome, grade 1 immune effector cell-associated neurotoxicity syndrome, and pneumonia that resulted in hospitalization. CONCLUSIONS: In this case series, CD19 CAR T-cell transfer appeared to be feasible, safe, and efficacious in three different autoimmune diseases, providing rationale for further controlled clinical trials. (Funded by Deutsche Forschungsgemeinschaft and others.).
EVALuna2:555903

Differences in Acute Graft-Versus-Host Disease (GVHD) Severity and Its Outcomes Between Black and White Patients - Rios, Carlos A.Ortega; Qayed, Muna; Etra, Aaron M.; Reshef, Ran; Newcomb, Richard; Yuhasz, Nicholas; Hexner, Elizabeth O.; Aguayo-Hiraldo, Paibel; Merli, Pietro; Hogan, William J.; Weber, Daniela; Kitko, Carrie L.; et al. (Transplantation and Cellular Therapy, 2024)
Acute graft-versus-host disease (GVHD) is a significant complication following hematopoietic stem cell transplantation (HCT). Although recent advancements in GVHD prophylaxis have resulted in successful HCT across HLA barriers and expanded access to HCT for racial minorities, less is known about how race affects the severity and outcomes of acute GVHD. This study examines differences in the clinical course of acute GVHD and the prognostic value of GVHD biomarkers for Black and White recipients. We conducted a retrospective analysis of patients in the Mount Sinai Acute GVHD International Consortium (MAGIC) database who underwent HCT between 2014 and 2021 to describe the difference in clinical course of acute GVHD and significance of GVHD biomarkers between Black and White recipients. We used propensity score matching to generate a 1:3 matched cohort of 234 Black patients and 702 White patients with similar baseline characteristics. In the first year after HCT Black patients experienced a higher cumulative incidence of grade III-IV acute GVHD (17% versus 12%, P = 0.050), higher nonrelapse mortality (NRM; 18% versus 12%, P = .009), and lower overall survival that trended toward statistical significance (73% versus 79%, P = .071) compared to White patients. The difference in NRM in the first year was even greater among Black patients who developed GVHD than White patients (24% versus 14%, P = .041). The distribution of low, intermediate, and high MAGIC biomarker scores at the time of treatment was similar across racial groups (P = .847), however, Black patients with high biomarker scores experienced significantly worse NRM than White patients (71% versus 32%, P = .010). Our data indicate that Black patients are at a higher risk of NRM following HCT, primarily from a higher incidence of severe GVHD. Serum biomarkers at treatment initiation can stratify patients for risk of NRM across races, however Black patients with high biomarker scores had a significantly greater NRM risk. These results suggest a need for strategies that mitigate the higher risk for poor GVHD outcomes among Black patients.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Acute GVHD; Biomarker; Race

Enasidenib in IDH-2 mutant AML patients with relapse after allogeneic stem cell transplantation - Vasova, Ingrid; Spörl, Silvia; Guggenberger, Valentin; Berisha, M.; Rech, D.; Behzad, Ali; Brandt, Amelie; Kremer, A.; Mackensen, Andreas; Rösler, Wolf; Winkler, J. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Expansion of Plasmablasts at Day 90 after Allogeneic Stem Cell Transplantation Predict Chronic Gvhd - Habenicht, Katharina Marie; Bootz, Anna; Schäfer, Simon; Vasova, Ingrid; Fante, Matthias; Schneider, Andrea; Rehli, Michael; Hoffmann, Petra; Rösler, Wolf; Edinger, Matthias; Herr, Wolfgang; Mackensen, Andreas; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Flares of acute graft-versus-host disease: a Mount Sinai Acute GVHD International Consortium analysis. - Akahoshi, Yu; Spyrou, Nikolaos; Hoepting, Matthias; Aguayo-Hiraldo, Paibel; Ayuk, Francis; Chanswangphuwana, Chantiya; Choe, Hannah K.; Eder, Matthias; Etra, Aaron M.; Grupp, Stephan A.; Hexner, Elizabeth O.; Hogan, William J.; et al. (Blood Advances, 2024)
The absence of a standardized definition for graft-versus-host disease (GVHD) flares and data on its clinical course are significant concerns. We retrospectively evaluated 968 patients across 23 Mount Sinai Acute GVHD International Consortium (MAGIC) transplant centers who achieved complete response (CR) or very good partial response (VGPR) within 4 weeks of treatment. The cumulative incidence of flares within 6 months was 22%, and flares were associated with a higher risk of nonrelapse mortality (NRM; adjusted hazard ratio [aHR], 4.84; 95% confidence interval [CI], 3.19-7.36; P < .001). Flares were more severe (grades 3/4, 41% vs 16%; P < .001) and had more frequent lower gastrointestinal (LGI) involvement (55% vs 32%; P < .001) than the initial GVHD. At CR/VGPR, elevated MAGIC biomarkers predicted the future occurrence of a flare, along with its severity and LGI involvement. In multivariate analyses, higher Ann Arbor (AA) biomarker scores at CR/VGPR were significant risk factors for flares (AA2 vs AA1: aHR, 1.81 [95% CI, 1.32-2.48; P = .001]; AA3 vs AA1: aHR, 3.14 [95% CI, 1.98-4.98; P < .001]), as were early response to initial treatment (aHR, 1.84; 95% CI, 1.21-2.80; P = .004) and HLA-mismatched unrelated donor (aHR, 1.74; 95% CI, 1.00-3.02; P = .049). MAGIC biomarkers also stratified the risk of NRM both at CR/VGPR and at the time of flare. We conclude that GVHD flares are common and carry a significant mortality risk. The occurrence of future flares can be predicted by serum biomarkers that may serve to guide adjustment and discontinuation of immunosuppression.
EVALuna2:563536

Low-dose interleukin-2 for the treatment of glucocorticoid-refractory acute graft-versus-host disease: a single center experience - Brandt, Adrian; Vasova, Ingrid; Winkler, Julia; Mackensen, Andreas; Rösler, Wolf; Spoerl, S.; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Measuring the cellular memory B cell response after vaccination in patients after allogeneic stem cell transplantation - Winkler, Julia; Tittlbach, Hannes; Schneider, Andrea; Buchstaller, Corinna; Mayr, Andreas; Vasova, Ingrid; Rösler, Wolf; Mach, Michael; Mackensen, Andreas; Winkler, Thomas (Annals of Hematology, 2020)
After allogeneic hematopoietic stem cell transplantation (HSCT), patients are repetitively vaccinated to reduce the risk of infection caused by the immune deficiency following allogeneic HSCT. By the vaccination of transplanted patients, the humoral memory function can be restored in the majority of cases. It is unknown, however, to what extent memory B cells derived from the donor contribute to the mobilization of antibody-secreting cells and long-term humoral memory in patients after allogeneic HSCT. We therefore analyzed patients after allogeneic HSCT for memory B cell responses 7 days after single vaccination against tetanus toxoid (TT), diphtheria toxoid (DT), pertussis toxoid (PT), Haemophilus influenzae type b (Hib), and poliovirus. Patients showed an insufficient mobilization of plasmablasts (PB) after vaccination, whereas healthy subjects (HD, n = 13) exhibited a significant increase of PB in the peripheral blood. Regarding vaccine-specific antibody-secreting PB, all HD responded against all vaccine antigens, as expected. However, only 65% of the patients responded with a measurable increase in IgG-secreting PB against TT, 65% against DT, 33% against PT, and 53% against poliovirus. Correspondingly, the antibody titers on day 7 after vaccination did not increase in patients. A significant increase of serum titers for the vaccine antigens was detectable in the majority of patients only after repetitive vaccinations. In contrast to the low mobilization of vaccine-specific PB after vaccination, a high number of PB before vaccination was detectable in patients following allogeneic HSCT. High frequencies of circulating PB correlated with the incidence of moderate/severe chronic GVHD. In summary, patients showed a weak mobilization of antigen-specific PB and an inadequate increase in antibody titers 7 days after the first vaccination. Patients with moderate or severe chronic GVHD in their history had a significantly higher percentage of IgG-secreting PB prior to vaccination. The antigen specificity of these IgG-secreting PB is currently unknown.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Allogeneic stem cell transplantation; Memory B cells; Plasmablast; Vaccination after transplantation

Novel MAGIC composite scores using both clinical symptoms and biomarkers best predict treatment outcomes of acute GVHD - Akahoshi, Yu; Spyrou, Nikolaos; Weber, Daniela; Aguayo-Hiraldo, Paibel; Ayuk, Francis; Chanswangphuwana, Chantiya; Choe, Hannah K.; Eder, Matthias; Etra, Aaron M.; Grupp, Stephan A.; Hexner, Elizabeth O.; Hogan, William J.; et al. (Blood, 2024)
Acute graft-versus-host disease (GVHD) grading systems that use only clinical symptoms at treatment initiation such as the Minnesota risk identify standard and high-risk categories but lack a low-risk category suitable to minimize immunosuppressive strategies. We developed a new grading system that includes a low-risk stratum based on clinical symptoms alone and determined whether the incorporation of biomarkers would improve the model's prognostic accuracy. We randomly divided 1863 patients in the Mount Sinai Acute GVHD International Consortium (MAGIC) who were treated for GVHD into training and validation cohorts. Patients in the training cohort were divided into 14 groups based on similarity of clinical symptoms and similar nonrelapse mortality (NRM); we used a classification and regression tree (CART) algorithm to create three Manhattan risk groups that produced a significantly higher area under the receiver operating characteristic curve (AUC) for 6-month NRM than the Minnesota risk classification (0.69 vs 0.64, P = .009) in the validation cohort. We integrated serum GVHD biomarker scores with Manhattan risk using patients with available serum samples and again used a CART algorithm to establish 3 MAGIC composite scores that significantly improved prediction of NRM compared to Manhattan risk (AUC, 0.76 vs 0.70, P = .010). Each increase in MAGIC composite score also corresponded to a significant decrease in day 28 treatment response (80% vs 63% vs 30%, P < .001). We conclude that the MAGIC composite score more accurately predicts response to therapy and long-term outcomes than systems based on clinical symptoms alone and may help guide clinical decisions and trial design.
CRIS-Team Scopus Importer:2024-08-09

Serial Clinical and Biomarker Monitoring during Graft-Versus-Host Disease Treatment Identifies Distinct Risk Strata Including an Ultra-Low Risk Group - Katsivelos, Nikolaos; Spyrou, Nikolaos; Weber, Daniela; Vasova, Ingrid; Ayuk, Francis; Choe, Hannah; Hogan, William; DeFilipp, Zachariah; Qayed, Muna; Etra, Aaron M.; Sandhu, Karam; Kraus, Sabrina; et al. (Transplantation and Cellular Therapy, 2025)
Background: The standard treatment for acute graft-vs-host disease (GVHD), a common complication following allogeneic hematopoietic cell transplant, remains prolonged courses of high dose corticosteroids. Previous attempts to decrease corticosteroid exposure during GVHD therapy failed because physicians lack the tools necessary to safely reduce and shorten therapy and fear loss of GVHD control in responding patients. Prior studies have shown that a serum biomarker risk score, the MAGIC algorithm probability (MAP), provided prognostic value within groups with similar clinical severity and that patients with GVHD that is Minnesota standard risk by clinical symptoms and who have a low MAP at the start of corticosteroid treatment represent a low risk group with good outcomes. Objective: This study tested the hypothesis that serial monitoring of GVHD symptoms and the MAP score in patients with low risk GVHD could provide further risk stratification, and would identify a subset with exceptionally low rates of failure with standard treatment, which we term ultra-low risk (ULR) GVHD who might benefit from reduced corticosteroid treatment. Study Design: Weekly monitoring of clinical symptoms and MAPs from initiation to day 14 of treatment was used to further divide 450 patients with low risk GVHD into groups with different outcomes, such as overall response rates at day 28 and non-relapse mortality at six-months. Results: 310/450 low risk patients (69%) who achieved clinical response by day 14 and had low MAPs at days 7 and 14 constituted an ultra-low risk (ULR) group. that experienced a significantly higher overall response rate at day 28 (93% vs 50%, p<0.001) that was sustained to day 56 (84% vs 45%, p<0.001) and significantly lower six-month NRM (4% vs 13%, p<0.001) compared to the non-ULR patients. Patients who achieved clinical response by day 14 but who developed a high MAP during monitoring (n=20) experienced six-fold higher six-month NRM than the ULR group (25% vs 4%, p<0.001). Among 120 patients who did not achieve a clinical response by day 14, the overwhelming majority (n=112) who maintained low MAPs at both days 7 and 14 of treatment experienced six-fold lower NRM at six months compared to patients with a high MAP at either time point (8% vs 50%, p<0.001). The majority of deaths within the ULR group were due to infections in patients with complete and sustained control of GVHD symptoms while the majority of deaths in the non-ULR group were due to poorly controlled GVHD. Conclusions: Serial monitoring during treatment can identify a large subset of patients by day 14 who achieve excellent GVHD control but remain at risk for treatment complications with standard treatment and who might be suitable candidates for testing abbreviated corticosteroid courses.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Acute GVHD; Biomarker; Immunosuppression; Treatment

The MAGIC algorithm probability predicts treatment response and long-term outcomes to second-line therapy for acute GVHD - DeFilipp, Zachariah; Kim, Haesook T.; Spyrou, Nikolaos; Katsivelos, Nikolaos; Kowalyk, Steven; Eng, Gilbert; Kasikis, Stelios; Beheshti, Rahnuma; Baez, Janna; Akahoshi, Yu; Ayuk, Francis; Choe, Hannah; et al. (Blood Advances, 2024)
The significance of biomarkers in second-line treatment for acute graft-versus-host disease (GVHD) has not been well characterized. We analyzed clinical data and serum samples at the initiation of second-line systemic treatment of acute GVHD from 167 patients from 17 centers of the Mount Sinai Acute GVHD International Consortium (MAGIC) between 2016 and 2021. Sixty-two patients received ruxolitinib-based therapy, whereas 102 received other systemic agents. In agreement with prospective trials, ruxolitinib resulted in a higher day 28 (D28) overall response Frate than nonruxolitinib therapies (55% vs 31%, P = .003) and patients who received ruxolitinib had significantly lower nonrelapse mortality (NRM) than those who received nonruxolitinib therapies (point estimates at 2-year: 35% vs 61%, P = .002). Biomarker analyses demonstrated that the benefit from ruxolitinib was observed only in patients with low MAGIC algorithm probabilities (MAPs) at the start of second-line treatment. Among patients with a low MAP, those who received ruxolitinib experienced significantly lower NRM than those who received nonruxolitinib therapies (point estimates at 2-year: 12% vs 41%, P = .016). However, patients with high MAP experienced high NRM regardless of treatment with ruxolitinib or nonruxolitinib therapies (point estimates at 2-year: 67% vs 80%, P = .65). A landmark analysis demonstrated that the relationship between the D28 response and NRM largely depends on the MAP level at the initiation of second-line therapy. In conclusion, MAP measured at second-line systemic treatment for acute GVHD predicts treatment response and NRM. The outcomes of patients with high MAP are poor regardless of treatment choice, and ruxolitinib appears to primarily benefit patients with low MAP.
CRIS-Team Scopus Importer:2024-07-19

Vaccination after Allogenic Stem Cell Transplantation: Diminished Memory B Cell Response and High Number of Spontaneously IgG Secreting Plasmablasts - Tittlbach, Hannes; Schneider, Andrea; Buchstaller, Corinna; Mayr, Andreas; Vasova, Ingrid; Rösler, Wolf; Mackensen, Andreas; Mach, Michael; Winkler, Thomas; Winkler, Jürgen (BLOOD, 2018)
CRIS-Team WoS Importer:2019-02-27